Penataan Kawasan Pasar Senen Sebagai Wujud Marketing Destination Kota Jakarta Oleh PERUMDA Pasar Jaya Tahun 2024 - Martiny, Mimy; Sumidartiny, Ai Netty (JAMBIS : Jurnal Administrasi Bisnis, 2024)
This research aims to investigate the potential, challenges, and opportunities related to the transformation of Pasar Senen which is attractive to local and international tourists. The method used in this research is a descriptive method with a qualitative approach. The data source used by researchers in this research was interview techniques. Based on the discussion, this research concludes that Pasar Senen as a marketing destination in Jakarta shows great potential for this market to continue to develop as an attractive shopping destination. By addressing problems through infrastructure revitalization, increased promotions, and improved service quality, this market can become a more attractive and sustainable shopping destination. Furthermore, the strategy for structuring the Pasar Senen area has proven its potential to increase its attractiveness as a prominent shopping destination in Jakarta.